Iron deficiency and iron‐deficiency anaemia in women's health. (April 2017) - Percy, Laura; Mansour, Diana
Abstract : Key content: Iron deficiency is the most common micronutrient deficiency worldwide. More than 20% of women are iron deficient in their reproductive years. There are a number of oral iron preparations available but iron content in them varies and they can result in gastrointestinal adverse effects. The formulation and dose of iron should be chosen to best suit the woman and her level of iron deficiency. As gynaecologists, we focus on reducing menstrual blood loss in women with heavy menstrual bleeding, but frequently fail to diagnose, manage and treat iron deficiency/iron‐deficiency anaemia, resulting in a slow return to improved quality of life. Learning objectives: To be able to summarise the mechanisms underlying iron metabolisms and the importance of iron in cellular functioning. To help clinicians recognise the importance of iron deficiency and its management. Ethical issues: Severe preoperative iron‐deficiency anaemia may place a patient at increased risk of blood transfusion during surgery and adverse postoperative sequelae. Recognising and treating this with intravenous iron can prevent such an intervention, but at the cost of providing treatment in a safe, appropriately staffed environment to manage rare adverse events such as anaphylaxis.